Characterization of Temperature Indices of Silicates - Khan, Abdul Rauf; Ghani, Muhammad Usman; Ghaffar, Abdul; Asif, Hafiz Muhammad; İnç, Mustafa (Springer, 2023)
A topological index is a numerical value that describes the entire structure of a chemical compound's molecular graph and aids in the understanding of its physical properties, chemical reactivities, and boiling activities. In chemical graph theory, these indices are instrumental in quantifying various chemical properties of chemical compounds such as SiO4. The selection of SiO4 in this work is an important aspect because of its structural flexibility, easy availability, and extraordinary nature to find its numerical values. In this paper, we compute systematically the first and second temperature, hyper temperature indices, the sum connectivity temperature index, the product connectivity temperature index, the reciprocal product connectivity temperature index, and the F temperature index of a molecular graph SiO4 embedded in a chain. All of the discussed interlinked networks in this manuscript are well motivated by the molecular structure of SiO4.
Keywords: Temperature indices; SiO4 embedded in a chain